Relative viability proxy of airborne prokaryotic microorganisms at the Southeastern Mediterranean coastal Sea - Rahav, E.; Paytan, A.; Herut, B. (Frontiers in Environmental Science, 2022)
The atmosphere plays a fundamental role in transporting airborne prokaryotes across the oceans and land. Despite the harsh atmospheric conditions, a considerable fraction of the airborne prokaryotic microorganisms survive the journey and remain viable upon deposition, and can affect the receiving environment. Here, we provide the first estimate of potential viability proxy for airborne prokaryotic cells at the Southeastern Mediterranean coast in 22 events during 2015, representing marine and terrestrial air-mass trajectories and a significant dust storm event. This was assessed using sequence amplicons of the small subunit ribosomal RNA gene (SSU rRNA) jointly with other complementary measurements. To estimate the relative viability in our dataset we used the ratio between the abundance of the bacterial SSU rRNA transcripts in a given sampling date and the lowest measured value (23.7.2015) as a measure of a ‘relative viability proxy. The abundance of prokaryotes SSU rRNA transcripts ranged from ~500 to 11000 copies m3, with ~2-fold higher relative viability proxy in marine-origin aerosols than predominantly terrestrial atmospheric trajectories. The relative viability proxy of prokaryotes was low during the peak of an intense and prolonged dust storm, and increased by ~1.5-fold in the subsequent days representing background conditions (<1700 ng Al m-3). Furthermore, we show that anthropogenic/toxic trace-metals (Cu/Al, Pb/Al) negatively correlates with potentially viable airborne prokaryotes in marine trajectory aerosols, whereas mineral dust load (Al, Fe proxy) positively affect their potential viability proxy. This may suggest that airborne prokaryotes associated to marine trajectories benefit from a particle-associate lifestyle, enabling relatively higher humidity and supply of nutrients attributed to mineral dust particles.